Reality and expectations of old-age pension savings in the pension system of the Slovak Republic - Peter Sika; Jarmila Vidová (Review of Economic Perspectives, 2021)
The aim of the authors is to provide a critical statistical-analytical view of the current pension system of the Slovak Republic with special regard to old -age pension savings in its fifteen-year existence, resulting in proposals for adjustments to its operation. It includes an analysis of the sustainability of pension systems, an analysis of the age distribution of savers as well as possible investment strategies of savers and the distribution of their property savings in pension funds. We model the investment strategy of a participant in old-age pension savings. We draw attention to the evaluation of old -age pension savings in pension funds during its existence and quantify the potential loss caused by an inappropriate investment strategy of savers. The an alysis showed that the Slovak participant in old-age pension savings invests mainly in conservative pension assets, which bring low volatility in the short term, which may not be optimal in the long run. In order to achieve change, we also outline the possibilities of changing the attitudes of savers to value their savings and propose reform steps that would contribute to ensuring a balance between the financial and social sustainability of the pension system.
Keywords: D31; G17; G22; G28; G51; G52; 330; demographic change; financing of pension systems; pension systemsocial security